Research Trend of Integration of Problem Based Learning in Laboratory Activities: A Bibliometric Analysis - Aulia Ajizah; N. Nahadi; Chairil Faif Pasani; Encep Syarief Nurdin (Postgraduate, University of Mataram, 2024)
This article is written to analyze the research trends regarding the integration of the Problem Based Learning (PBL) model in laboratory practical activities over the past 10 years (2014–2023). The method employed is Bibliometric Analysis, supported by the VOSviewer application. The analysis focused on titles and abstracts, encompassing 961 scientific articles from international journals indexed in Scopus over the last decade. Data collection was performed through searches using the keyword